Author Correction: Antimicrobial Peptide Potency is Facilitated by Greater Conformational Flexibility when Binding to Gram-negative Bacterial Inner Membranes. Issue 1 (December 2018) - Amos, Sarah-Beth; Vermeer, Louic; Ferguson, Philip; Kozlowska, Justyna; Davy, Matthew; Bui, Tam; Drake, Alex; Lorenz, Christian; Mason, A.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.